2022
DOI: 10.3389/fpls.2022.1075488
|View full text |Cite
|
Sign up to set email alerts
|

Spraying sorbitol-chelated calcium affected foliar calcium absorption and promoted the yield of peanut (Arachis hypogaea L.)

Abstract: The prevalent use of foliar calcium fertilizers in peanut production is inorganic, but calcium absorbed from the foliar has poor availability. Sorbitol-chelated calcium is a novel organic foliar calcium fertilizer that has rarely been studied for application in peanut production. To explore whether calcium absorption and peanut yields can be affected by foliar application of sorbitol-chelated calcium, this study conducted two field experiments using Virginia peanut (Huayu-22) in 2020 and 2021. The five spray t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Likewise, the application of Sorbitol-chelated calcium throughout the crop cycle increased leaf calcium concentration by 13.12-19.32% and kernel calcium concentration by 6.49-8.15% compared to the control in peanuts [52] and total calcium and calcium bound in leaves and fruits of pepper plants [53]. This chelation of calcium with polyols converts inorganic calcium to organic, enabling a vectoring process for absorption, translocation, and transformation [54].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the application of Sorbitol-chelated calcium throughout the crop cycle increased leaf calcium concentration by 13.12-19.32% and kernel calcium concentration by 6.49-8.15% compared to the control in peanuts [52] and total calcium and calcium bound in leaves and fruits of pepper plants [53]. This chelation of calcium with polyols converts inorganic calcium to organic, enabling a vectoring process for absorption, translocation, and transformation [54].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the physiological and biochemical processes and growth of peanuts may be impacted by the greater calcium concentrations in leaves and stems, which could also indirectly alter the soil's ability to absorb calcium. [23]. Also, the calcium foliar application improved leaf growth and dry weight [24].…”
Section: Peanut Growth and Yield Components Traitsmentioning
confidence: 94%
“…This result may be due to poor availability and absorption of foliar calcium application. Li et al [23] reported that inorganic foliar calcium fertilizers are frequently used in the production of peanuts. However, calcium absorbed through the foliar has low availability.…”
Section: Peanut Growth and Yield Components Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on soybeans by Sugimoto et al have revealed that spraying calcium formate and calcium nitrate boosts defensive enzyme activities, significantly inhibiting the occurrence of soybean stem rot, indicating that calcium, as an important signaling molecule, can improve plant disease resistance by regulating specific antioxidant enzymes, such as superoxide dismutase, catalase, peroxidase, and ascorbate peroxidase [33,34]. Furthermore, exogenous calcium also plays a very important role in enhancing the stress resistance and improving the quality of peanuts [35][36][37]. However, compared to vegetables and crops, the mechanism of calcium-induced resistance in peanuts is still not clear.…”
Section: Introductionmentioning
confidence: 99%